A novel approach to estimate carbon loss from drained peatlands in Iceland - Gunnhildur Eva G. Gunnarsdóttir 1993- (2017)
In the last century, the conversion of peatlands to grasslands through drainage was a popular method employed in Iceland to increase agricultural yields. Peatland drainage releases carbon dioxide into the atmosphere, thereby contributing to global climate change. According to Iceland´s National Inventory Reports, using global emission standards recommended by the Intergovernmental Panel on Climate Change, the greatest single source of GHG emissions in Iceland comes from drained land. Only limited research has been done to estimate carbon loss from drained peat soils in Iceland. In this paper I introduce a new approach for estimating carbon loss from uncultivated peat soils by using tephrochronology. Samples were collected in eight peatland sites in South and Southwest Iceland that had parts that were drained and parts that were unaffected by drainage. Carbon stocks were calculated using measured carbon content and bulk density in reference to the depth down to a specific volcanic tephra layer. The difference in carbon stocks between the wet and well-drained areas represented carbon loss since drainage. The results showed a range of 0.7-3.1 tCha-1yr-1 that had been lost by drainage from the soil layer in question. This is on par with other studies in Iceland and elsewhere in the boreal climatic zone, supporting further use of the presented method. The results also confirmed that carbon loss has been ongoing since drainage. The results from this study help predict future carbon loss from drained peat soils in Iceland. Furthermore, they support restoration of peat soils as a mitigation strategy. Á Íslandi átti sér stað víðtæk framræsla votlendis á seinni hluta síðustu aldar. Með ríkisstyrkjum voru votlendi þurrkuð upp og þeim umbreytt í graslendi í því skyni að auka landbúnaðarframleiðslu landsins. Við framræslu votlendis losnar meðal annars gróðurhúsalofttegundin koltvísýringur út í andrúmsloftið og stuðlar að hlýnun jarðar. Samkvæmt þjóðarbókhaldi Íslands um losun gróðurhúsaloftegunda sem byggir á ...